Influence of Aeta Education in St. Francis Learning Center at Nibangon Subic, Zambales (American Journal of Multidisciplinary Research and Innovation, 2024)
The Aeta community is one of the indigenous peoples in the Philippines, and they face challenges in accessing quality education. These challenges include limited school infrastructure and resources, a lack of qualified teachers understanding their cultural context, and socio-economic barriers preventing Aeta children from attending school. Hence, this study explored the perception of Aeta students in their education at St. Francis Learning Center. Specifically, it determined the socio-demographic profile of the participants in terms of year level, gender, age, family members, and socio-economic status; their perception on course descriptions, laboratory experiences, and the quality of academic staff; the factors that influence their decision-making process; and their suggested intervention programs to motivate students to choose the specific Senior High School Strand and college. This study employed a mixed-method research design particularly the explanatory-sequential approach. The participants comprised 10 Aeta Students currently studying at St. Francis Learning Center for the academic year 2024-2025. Results showed that while some students find the course descriptions and teaching methods effective and engaging, others face significant challenges. Scenarios such as teachers being unprepared, insufficient class time, lack of learning materials, and ineffective repetition of lessons point to areas where the educational experience can be improved. Practical utility, economic potential, parental influence, peer relationships, personal interests, career aspirations, and familial roles all play critical roles influence the students’ decision-making processes when choosing their Senior High School tracks.